Student retention in Indonesian private university - Yulianti Talar; Jimmy Gozaly (International Journal of Evaluation and Research in Education (IJERE), 2020)
Private universities require more effort to retain student students so that these students can complete their studies and then work in the community. Through this research, input will be given to the study program regarding the improvement that must be made so that the private university can compete with the public university and educate the nation's children. Data collection was obtained through questionnaires and observations to 209 students. Data processed by Discriminant Analysis, Crosstabulations, and Correlations Analysis dan statistical descriptive methods. Independent variables that significantly affect student retention are satisfaction with the closeness of social relationships with fellow students, student confidence to graduate on time, student confidence to get a good career after graduation, and college attendance. Study program still has to work hard to make improvements to increase satisfaction and students' engagement level.